Suppressor of cytokine signaling proteins as regulators of innate immune signaling - Strebovsky, Julia; Walker, Patrick; Dalpke, Alexander (Frontiers in bioscience. Landmark, 2012)
The innate immune system builds up the body's first line of defense against invading pathogenic microorganisms. For effective defense of pathogenic invaders, a structured inflammatory reaction has to be initiated that is strongly dependent on cell-to-cell communication. Inflammation in turn is a potentially autodestructive reaction that is tightly controlled to balance antimicrobial activity and host damage. Suppressor of cytokine signaling (SOCS) proteins have been identified as crucial negative regulators of various hematopoietic cytokines employing Janus kinas (JAK) and signal transducer and activator of transcription (STAT) signaling. Further results now imply that also signaling by pattern recognition receptors (PRR) of the innate immune system that use a distinct signaling cascade induce and get regulated by SOCS proteins. Thus, SOCS proteins not only modulate cell communication through JAK/STAT dependent cytokines but also regulate signaling by pattern recognition receptors including the Toll-like receptors (TLRs). A model is presented that integrates the current, partly conflicting, data on the role of SOCS proteins in innate immunity's NFkappaB signaling.